The Value of Natural Resources and Their Ecosystem Services for Society: A Methodical and Empirical Analysis from CINPE-UNA - Moreno Díaz , Mary Luz (2025)
The economic valuation processes of natural resources and their ecosystem services are supported by a theoretical and methodological framework that has evolved over the years. The International Center of Economic Policy for Sustainable Development (CINPE) has applied this rigorous framework while adapting it to the specific needs of valuation in contexts involving non-use values, such as protected wild areas. This essay reviews the general conceptual and theoretical foundations, followed by an analysis of the results obtained from valuation processes and the methodologies employed. The essay concludes that CINPE has progressively adapted its valuation approaches in response to emerging developments, maintaining scientific rigor throughout. Moreover, the results have been crucial for the management of natural resources and their ecosystem services in the context of Costa Rica